Persistence of SARS-CoV-2 RNA shedding and infectivity in immunized population: Prospective study along different epidemiological periods in Argentina. - Clara Theaux; Yamila Martin; Luciana Montoto Piazza; Gretel Wenk; Guillermo Notaristefano; Laura Miño; María Eugenia Sevilla; Valeria Aprea; Aldana Claps; Mercedes Nabaes Jodar; Dolores Acuña; Melina Salvatori; et al. (PLoS ONE, 2023)
During the pandemic of COVID-19, numerous waves of infections affected the two hemispheres with different impacts on each country. Throughout these waves, and with the emergence of new variants, health systems and scientists have tried to provide real-time responses to the complex biology of SARS-CoV-2, dealing with different clinical presentations, biological characteristics, and clinical impact of these variants. In this context, knowing the extent period in which an infected individual releases infectious viral particles has important implications for public health. This work aimed to investigate viral RNA shedding and infectivity of SARS-CoV-2 beyond 10 days after symptom onset (SO). A prospective multicenter study was performed between July/2021 and February/2022 on 116 immunized strategic personnel with COVID-19 diagnosed by RT-qPCR, with asymptomatic (7%), mild (91%) or moderate disease (2%). At the time of diagnosis, 70% had 2 doses of vaccines, 26% had 2 plus a booster, and 4% had one dose. After day 10 from SO, sequential nasopharyngeal swabs were taken to perform RT-qPCR, viral isolation, and S gene sequencing when possible. Viral sequences were obtained in 98 samples: 43% were Delta, 16% Lambda, 15% Gamma, 25% Omicron (BA.1) and 1% Non-VOC/VOI, in accordance with the main circulating variants at each moment. SARS-CoV-2 RNA was detected 10 days post SO in 57% of the subjects. Omicron was significantly less persistent. Noteworthy, infective viruses could not be isolated in any of the samples. In conclusion, a 10-days isolation period was useful to prevent further infections, and proved valid for the variants studied. Recently, even shorter periods have been applied, as the Omicron variant is prevalent, and worldwide population is largely vaccinated. In the future, facing the possible emergence of new variants and considering immunological status, a return to 10 days may be necessary.